2013
DOI: 10.1007/s00709-013-0543-6
|View full text |Cite
|
Sign up to set email alerts
|

A milestone in the doubled haploid pathway of cassava

Abstract: This study was aimed at inducing androgenesis in cultured anthers of cassava (Manihot esculenta Crantz) to develop a protocol for the production of doubled haploids. Microspore reprogramming was induced in cassava by cold or heat stress of anthers. Since the anthers contain both haploid microspores and diploid somatic cells, it was essential to verify the origin of anther-derived calli. The origin of anther-derived calli was assessed by morphological screening followed by histological analysis and flow cytomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 45 publications
0
22
0
2
Order By: Relevance
“…Higher concentration (5–10 mg l -1 ) of 2,4-D stimulated ME initiation in some recalcitrant plant species, namely oat ( Kiviharju and Tauriainen, 1999 ), Triticum turgidum ( Jauhar, 2003 ), and cassava ( Perera et al, 2014 ). It has been suggested that 2,4-D is not only an auxin analog but at higher concentrations acts as a stress factor effectively triggering embryogenic pathway of cell development ( Gaj, 2004 ).…”
Section: New Concepts Describing Pgrs Involvement In Me Regulationmentioning
confidence: 99%
“…Higher concentration (5–10 mg l -1 ) of 2,4-D stimulated ME initiation in some recalcitrant plant species, namely oat ( Kiviharju and Tauriainen, 1999 ), Triticum turgidum ( Jauhar, 2003 ), and cassava ( Perera et al, 2014 ). It has been suggested that 2,4-D is not only an auxin analog but at higher concentrations acts as a stress factor effectively triggering embryogenic pathway of cell development ( Gaj, 2004 ).…”
Section: New Concepts Describing Pgrs Involvement In Me Regulationmentioning
confidence: 99%
“…However, they result in either homozygous or heterozygous spontaneous DHs. The formation of homozygous DHs was caused by endomitosis/endoreduplication, while the heterozygous ones were caused by nuclear fusion (Perera et al, 2014). According to Perera et al (2008), homozygous versus heterozygous lines can be determined by SSR marker analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Plant improvement through double-haploid technology makes it possible to obtain thousands of plants that must be properly analyzed, because of ploidy level and haplotype variation among individuals (Zagorska et al 1997, Seguí-Simarro & Nuez 2007, Perera et al 2014. Thus, FCM emerges as an effective alternative to determine changes in ploidy ( Fig.…”
Section: Double Haploid Technique and Fcmmentioning
confidence: 99%